Francisco García Jurado, Borges, autor de la Eneida. Poética del laberinto, Madrid, Biblioteca ELR Ediciones, 2006, 130 págs. ISBN 84-87607-17-9 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Francisco García Jurado, Borges, autor de la Eneida. Poética del laberinto, Madrid, Biblioteca ELR Ediciones, 2006, 130 págs. ISBN 84-87607-17-9